HOW HAS OPTIMALITY THEORY ACHIEVED THE GOALS OF LINGUISTIC THEORY - Abdurrahman, Israa .B (Al-Adab Journal, 2015)
Optimality Theory (OT) is a grammatical framework of recent origin presented by Prince and Smolensky in 1993. The central idea of Optimality Theory is that surface forms of language reflect resolutions of conflicts between competing constraints. A surface form is ‘optimal’ in the sense that it incurs the least serious violations of a set of violable constraints, ranked in a language-specific hierarchy. Constraints are universal and languages differ in the ranking of constraints, giving priorities to some constraints over others. Such rankings are based on ‘strict’ domination: if one constraint outranks another, the higher-ranked constraint has priority, regardless of violations of the lower-ranked one. However, such violation must be minimal, which predicts the economy property of grammatical processes. This paper tries to seek the clues to prove that optimality theory achieves the goals of linguistic theory successfully